UTG high-impact-resistance protective sticker for folding display screen and preparation process thereof
Patent Information
- Application Number
- CN202611015038.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-09
AI Technical Summary
[0005]为了解决上述现有技术中存在的贴合性能、抗冲击性能差的技术问题,本发明提供了一种UTG折叠显示屏用高抗冲击性保护贴及其制备工艺
(1)本发明在环氧树脂分子结构中引入二硫键,赋予环氧树脂膜层微小裂纹损伤自修复能力,提升环氧树脂层与UTG层的贴合性能;
Smart Images

Figure CN122518812B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite structure protective film technology, specifically relating to a high impact-resistant protective film for UTG foldable displays and its preparation process. Background Technology
[0002] With the rapid development of flexible foldable display technology, ultra-thin glass (UTG) has become the mainstream substrate for high-end foldable screen cover plates due to its high hardness, high light transmittance, and excellent crease resistance. To improve drop resistance, impact resistance, and structural stability, the industry generally adopts a double-layer UTG composite structure, using thermoplastic epoxy resin as a transparent coupling adhesive and buffer layer between the layers.
[0003] Existing UTG screen protectors suffer from significant problems when used in small-radius, high-frequency dynamic folding and complex environments, including modulus mismatch, interface failure, difficulty in balancing impact resistance and foldability, and dynamic fatigue optical degradation. These issues severely impact the reliability and lifespan of foldable screens. Current technologies still have the following technical shortcomings: First, the significant difference in modulus between UTG and thermoplastic epoxy resin leads to excessively high interfacial shear stress, making interlayer failure likely. UTG has a Young's modulus of approximately 70 GPa, while thermoplastic epoxy resin has a modulus of only a few hundred MPa to a few GPa. Their deformation is asynchronous, resulting in significant periodic shear stress at the interface under high-frequency dynamic folding. This easily triggers creep slippage in the resin layer, leading to interfacial debonding, bubbles, creases, and even stress reversal causing UTG brittle fracture. Second, it is difficult to simultaneously meet impact resistance and toughness requirements. Puncture resistance and point impact resistance require sufficient material thickness and rigidity to disperse high stress, while small-radius folding requires a low modulus and high flexibility in the resin layer. If the resin is too soft, it is easily punctured by sharp objects and damages the UTG. If it is too hard, the bending stiffness is too high, making it impossible to achieve low curvature folding and easily causing hinge fatigue damage. Third, the resin has poor durability. Thermoplastic epoxy resin is prone to molecular chain orientation and silvering under long-term alternating stress, resulting in stress whitening and increased haze. It is prone to aging and yellowing in humid and hot environments and light exposure, reducing the visual effect and structural durability of the display. As an optically transparent layer, the resin is prone to microphase separation and uneven refractive index under repeated tensile and compressive strain and environmental erosion, resulting in increased haze, decreased light transmittance, and bright lines in the folded area, making it difficult to meet the requirements of long-term optical stability.
[0004] Chinese patent application CN119445980A discloses a flexible screen cover, a flexible screen, and a foldable electronic device. The flexible screen cover includes ultra-thin glass, a first buffer coating, and a second buffer coating. The ultra-thin glass has a first surface and a second surface disposed opposite to each other. The first buffer coating is disposed on the first surface, and the second buffer coating is disposed on the second surface. The first and second buffer coatings provide physical protection to both the first and second surfaces of the ultra-thin glass, improving its impact resistance. The material of the first buffer coating includes any one or more of acrylic resin, silicone resin, epoxy resin, and polyurethane resin. The material of the second buffer coating includes any one or more of acrylate-modified polyurethane, epoxy-modified polyurethane, hyperbranched polyurethane, acrylic resin, silicone resin, and epoxy resin. However, the patent application only applies to surface coating protection for single-layer ultrathin glass, which cannot be applied to double-layer UTG composite structures. It does not solve technical problems such as interlayer modulus mismatch, asynchronous deformation, and shear stress concentration. Under dynamic folding, interlayer slippage, debonding and bubbling, and UTG brittle fracture are still prone to occur. Moreover, its buffer layer only uses simple resins such as conventional acrylate, epoxy resin, and polyurethane, without viscoelastic adaptive design, and cannot take into account both low-radius folding flexibility and high-speed impact resistance. Summary of the Invention
[0005] To address the technical problems of poor adhesion and impact resistance in the existing technology, this invention provides a high impact-resistant protective film for UTG foldable displays and its preparation process.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows:
[0007] A high-impact protective film for a UTG foldable display screen comprises, from top to bottom, a base film layer, a modified epoxy resin layer, a modified UTG layer, a modified epoxy resin layer, a modified UTG layer, a modified epoxy resin layer, and an OCA adhesive film layer. The modified epoxy resin layer is prepared by dissolving a linear thermoplastic epoxy resin containing disulfide bonds in a mixed solution of butanone and ethyl acetate, adding boron-siloxane-grafted silica nano-dispersion, ultrasonically dispersing it evenly, coating it, and drying it to obtain the modified epoxy resin layer.
[0008] In the above scheme, the molecular skeleton of linear thermoplastic epoxy resin containing disulfide bonds endows the resin-like glass polymer with the properties of a polymer and has good viscoelasticity. It can effectively absorb and buffer the interfacial shear stress brought by the double-layer UTG. Even after hundreds of thousands of folds, when the interface or resin produces tiny silver streaks or interfacial slip due to stress fatigue, the dynamic disulfide bonds in the resin will undergo a dynamic exchange reaction under the conditions of room temperature or the slight heat emitted by the screen itself, reconnecting the broken polymer chains and self-healing the microcracks. At the same time, the thiol groups on the surface of the modified UTG layer synergistically with the disulfide bonds of the resin to improve the adhesion between the UTG layer and the resin layer. Boron-siloxane is a typical shear-thickening material that can undergo a reversible liquid-solid phase transition with increasing strain rate in a very short time. Under slow folding (low shear rate), the boric acid bonds and siloxane chains are in a relaxed state. When subjected to external force such as a drop or a sharp stylus pen puncture (this is a high strain rate / instantaneous high shear), the boron-siloxane network instantly undergoes polar cross-linking, diffusing the huge energy of the point impact in all directions, effectively protecting the UTG from puncture damage and improving the impact resistance of the protective film.
[0009] Furthermore, the preparation method of the linear thermoplastic epoxy resin containing disulfide bonds is as follows: nitrogen gas is introduced into the reaction vessel to replace the air inside the vessel, then bisphenol A type epoxy resin and 4,4'-dihydroxydiphenyl disulfide are added, N,N-dimethylacetamide is added to adjust the solid content to 20%-30%, the mixture is heated to 80-85℃ and stirred to dissolve, the temperature is raised to 130-140℃ and triphenylphosphine is added, the mixture is kept at this temperature for 6-8 hours under stirring, the temperature is cooled to 60-70℃, acetone is added for dilution, and then the mixture is added dropwise to deionized water under high-speed stirring. The polymer precipitates to form a precipitate, which is then filtered, washed, and dried to obtain the linear thermoplastic epoxy resin containing disulfide bonds.
[0010] In the above scheme, 4,4'-dihydroxydiphenyl disulfide is used as a chain extender. Under the catalysis of triphenylphosphine, it undergoes an epoxy-phenolic hydroxyl ring-opening addition polymerization reaction with bisphenol A type epoxy resin, thereby introducing the disulfide bonds in 4,4'-dihydroxydiphenyl disulfide into the epoxy resin, resulting in a linear thermoplastic modified epoxy resin with dynamic disulfide bonds in the main chain and epoxy active groups retained at the end groups. The epoxy end groups in the modified epoxy resin molecule can form chemical bonds with the hydroxyl groups on the UTG surface. The disulfide bonds can undergo a dynamic reversible reaction of bond breaking and recombination under slight heating or pressure, autonomously repairing the micro-crack damage caused by folding, thereby effectively improving the bonding force between the UTG layer and the epoxy resin layer.
[0011] Furthermore, in the preparation method of the linear thermoplastic epoxy resin containing disulfide bonds, the molar ratio of the epoxy group in the bisphenol A type epoxy resin to the phenolic hydroxyl group in 4,4'-dihydroxydiphenyl disulfide is (1.02-1.05):1.
[0012] In the above scheme, the molar ratio of the epoxy group in the bisphenol A type epoxy resin to the phenolic hydroxyl group in 4,4'-dihydroxydiphenyl disulfide directly determines the molecular structure and end group type of the modified epoxy resin. Controlling a slight excess of epoxy groups can terminate chain growth, maintain the linear thermoplastic structure of the modified epoxy resin, and ensure that the end groups are epoxy groups to participate in subsequent reactions.
[0013] Furthermore, in the preparation method of the linear thermoplastic epoxy resin containing disulfide bonds, the amount of triphenylphosphine used is 0.1%-0.3% of the total mass of bisphenol A type epoxy resin and 4,4'-dihydroxydiphenyl disulfide.
[0014] Furthermore, the preparation method of boron-siloxane-grafted silica nano-dispersion is as follows: nitrogen gas is introduced into the reaction vessel to replace the air inside the vessel, and boric acid, dimethyldimethoxysilane and ethanol aqueous solution are added under nitrogen protection. Dibutyltin dilaurate is added, the temperature is raised to 100-110℃ and refluxed for 6-8 hours. Nano-silica is added, the temperature is raised to 120-130℃, and ultrasonic dispersion is carried out under stirring for 10-12 hours. After cooling, the pH value is adjusted to 5-7, filtered, and ethanol aqueous solution is added to adjust the solid content to 15%-20% to obtain boron-siloxane-grafted silica nano-dispersion.
[0015] In the above scheme, boric acid and dimethyldimethoxysilane undergo a de-alcoholization condensation reaction under the catalysis of dibutyltin dilaurate to generate borosilicate prepolymer. Then, the prepolymer undergoes dehydration condensation with the silanol groups on the surface of nano-silica through its terminal hydroxyl and alkoxy groups. Under the synergistic effect of ultrasound and stirring, it is grafted onto the surface of nano-silica to form a borosilicate-silica grafted nano-dispersion with excellent dispersion.
[0016] Furthermore, in the preparation method of boron-siloxane grafted silica nano-dispersion, the mass parts of boric acid, dimethyldimethoxysilane, ethanol aqueous solution, dibutyltin dilaurate, and nano-silica are as follows: boric acid 3-8 parts, dimethyldimethoxysilane 10-20 parts, ethanol aqueous solution 70-85 parts, dibutyltin dilaurate 0.1-0.5 parts, and nano-silica 15-25 parts; the mass percentage of the ethanol aqueous solution is 80%-90%.
[0017] Furthermore, in the method for preparing the modified epoxy resin layer, the amount of boron-siloxane-grafted silica is 3%-5% of the mass of the linear thermoplastic epoxy resin containing disulfide bonds.
[0018] Furthermore, the modified UTG layer is prepared as follows: the upper and lower surfaces of the UTG are scanned and treated with atmospheric pressure argon-oxygen mixed plasma at room temperature to obtain surface-treated UTG; γ-glycidyl etheroxypropyltrimethoxysilane and bis-[3-(triethoxysilyl)propyl]-disulfide are dissolved in an aqueous solution of isopropanol, the pH is adjusted to 4.5-5.0, and the solution is stirred for 2-2.5 h to obtain a composite silane hydrolysate; the surface-treated UTG is immersed in the composite silane hydrolysate for 30-60 s, and then vacuum dried at 110-120℃ for 15-20 min to obtain the modified UTG layer.
[0019] In the above scheme, a transition layer is formed on the UTG surface using γ-glycidyl etheroxypropyltrimethoxysilane and bis-[3-(triethoxysilyl)propyl]-disulfide, which disperses the polar shear stress at the interface into a three-dimensional network stress, thereby improving the adhesion between UTG and modified epoxy resin. After activation by atmospheric pressure argon-oxygen mixed plasma, the surface of UTG is covered with highly active free hydroxyl groups. After immersion in the composite silane hydrolysate, the silanol groups of the silane oligomers in the solution are tightly adsorbed with the free hydroxyl groups on the UTG surface through hydrogen bonds. During vacuum drying, the silanol groups in γ-glycidyl etheroxypropyltrimethoxysilane and bis-[3-(triethoxysilyl)propyl]-disulfide undergo a dehydration condensation reaction with the silanol groups on the UTG surface, causing the transition layer to adhere tightly to the UTG surface. Furthermore, during the preparation of the protective film, the epoxy functional groups of γ-glycidoxypropyltrimethoxysilane undergo a ring-opening addition reaction with the curing network in the modified epoxy resin matrix. The disulfide bonds in bis-[3-(triethoxysilyl)propyl]-disulfide generate free radicals under thermal excitation, which exchange with the dynamic disulfide bonds inside the modified epoxy resin, effectively improving the bonding force between the UTG layer and the epoxy resin layer.
[0020] Furthermore, in the method for preparing the modified UTG layer, the power of the atmospheric pressure argon-oxygen mixed plasma is 500-600W, and the scanning time is 25-30s.
[0021] Furthermore, in the preparation method of the modified UTG layer, the molar ratio of γ-glycidyl etheroxypropyltrimethoxysilane and bis-[3-(triethoxysilyl)propyl]-disulfide is (3-5):1; and the mass percentage of the aqueous solution of isopropanol is 65%-70%.
[0022] Furthermore, the base film layer is a polyimide resin film; the OCA adhesive film layer is an acrylic folded OCA adhesive film; the thickness of the base film layer is 25-75 μm, the thickness of the modified epoxy resin layer is 20-60 μm, the thickness of the modified UTG layer is 30-70 μm, and the thickness of the OCA adhesive film layer is 40-80 μm.
[0023] The present invention also provides a method for preparing the high impact-resistant protective film for the UTG foldable display screen, specifically: a base film layer is laminated with a modified epoxy resin layer, and then a modified UTG layer, a modified epoxy resin layer, a modified UTG layer, a modified epoxy resin layer and an OCA adhesive film layer are sequentially laminated on the modified epoxy resin layer, and the lamination is performed by a fully automatic hot press laminating machine, and then cut to obtain the high impact-resistant protective film for the UTG foldable display screen.
[0024] In the above solution, the use of a fully automatic hot-press laminating machine to prepare a high-impact protective film for UTG foldable displays through a hot-pressing process can effectively prevent delamination between film layers, improve the adhesion of the protective film, and thus extend its service life.
[0025] Compared with the prior art, the high impact-resistant protective film for UTG foldable displays and its preparation method provided by the present invention have the following technical advantages: (1) The present invention introduces disulfide bonds into the molecular structure of epoxy resin, which endows the epoxy resin film with the ability to self-repair micro-crack damage and improves the adhesion performance between the epoxy resin layer and the UTG layer. (2) In this invention, boron-siloxane-grafted silica nanoparticles are added to the epoxy resin layer to improve the impact resistance of the protective film. (3) The present invention coats the UTG surface with a bifunctional silane coupling agent transition layer containing epoxy and mercapto groups, which effectively improves the bonding force between UTG and modified epoxy resin layer. Attached Figure Description
[0026] Figure 1 Infrared spectrum of the linear thermoplastic epoxy resin containing disulfide bonds prepared in Example 4. Detailed Implementation
[0027] The following description, in conjunction with specific embodiments, provides further details, but the present invention is not limited to these embodiments. Those skilled in the art can make various modifications based on the fundamental principles of the present invention, but such modifications are all within the scope of the invention as long as they do not depart from its basic principles.
[0028] In this specific embodiment, the base film layer is a polyimide resin film, and the OCA adhesive film layer is an acrylic folded OCA adhesive film, both of which are commercially available products. The bisphenol A type epoxy resin is E-51, with an epoxy equivalent of 192 g / eq.
[0029] Preparation Example 1 The preparation method of linear thermoplastic epoxy resin containing disulfide bonds is as follows: High-purity nitrogen gas is introduced into the reaction vessel to replace the air in the vessel for 30 minutes to prevent the disulfide bonds from being oxidized and decomposed at high temperature during the polymerization process. Then, 195.84 g of dried bisphenol A type epoxy resin and 125.17 g of dried 4,4'-dihydroxydiphenyl disulfide are added. N,N-dimethylacetamide is added to adjust the solid content to 20%. The mixture is heated to 80°C and stirred to dissolve. After heating to 130°C, 0.32 g of triphenylphosphine is added. The mixture is kept at this temperature for 6 hours under stirring. After cooling to 60°C, 500 mL of acetone is added for dilution. Then, the mixture is added dropwise to deionized water under high-speed stirring. The polymer precipitates to form a precipitate. The precipitate is filtered, washed three times with anhydrous ethanol, and dried under vacuum at 80°C for 24 hours to obtain linear thermoplastic epoxy resin containing disulfide bonds.
[0030] The preparation method of boron-siloxane-grafted silica nano-dispersion is as follows: Nitrogen gas is introduced into the reaction vessel to replace the air inside the vessel, and 3g of boric acid, 20g of dimethyldimethoxysilane and 70g of 80% ethanol aqueous solution are added under nitrogen protection. 0.1g of dibutyltin dilaurate is added, and the mixture is heated to 100℃ and refluxed for 6h. 15g of nano-silica is added, and the mixture is heated to 120℃ and ultrasonically dispersed under stirring for 10h. After cooling, the pH value is adjusted to 5, and the mixture is filtered using a 0.2μm pore size filter membrane. The solid content is adjusted to 15% by adding ethanol aqueous solution to obtain boron-siloxane-grafted silica nano-dispersion.
[0031] The modified epoxy resin layer is prepared as follows: 100g of linear thermoplastic epoxy resin containing disulfide bonds is dissolved in a mixed solution of butanone and ethyl acetate (the volume ratio of butanone to ethyl acetate is 7:3), the solid content is controlled at 25%, 3g of boron-siloxane grafted silica nano-dispersion is added, ultrasonically dispersed at 20kHz for 30min, coated, and dried at 60℃ for 12h to obtain the modified epoxy resin layer.
[0032] Preparation Example 2 The preparation method of linear thermoplastic epoxy resin containing disulfide bonds is as follows: High-purity nitrogen gas is introduced into the reaction vessel to replace the air in the vessel for 30 minutes to prevent the disulfide bonds from being oxidized and decomposed at high temperature during the polymerization process. Then, 201.6 g of dried bisphenol A type epoxy resin and 125.17 g of dried 4,4'-dihydroxydiphenyl disulfide are added. N,N-dimethylacetamide is added to adjust the solid content to 30%. The mixture is heated to 85°C and stirred to dissolve. After heating to 140°C, 0.98 g of triphenylphosphine is added. The mixture is kept at this temperature for 8 hours under stirring. After cooling to 70°C, 500 mL of acetone is added for dilution. Then, the mixture is added dropwise to deionized water under high-speed stirring. The polymer precipitates to form a precipitate. The precipitate is filtered, washed three times with anhydrous ethanol, and dried under vacuum at 90°C for 26 hours to obtain linear thermoplastic epoxy resin containing disulfide bonds.
[0033] The preparation method of boron-siloxane-grafted silica nano-dispersion is as follows: Nitrogen gas is introduced into the reaction vessel to replace the air inside the vessel, and 8g of boric acid, 10g of dimethyldimethoxysilane and 85g of 90% ethanol aqueous solution are added under nitrogen protection. 0.5g of dibutyltin dilaurate is added, and the mixture is heated to 110℃ and refluxed for 8h. 25g of nano-silica is added, and the mixture is heated to 130℃ and ultrasonically dispersed for 12h under stirring. After cooling, the pH value is adjusted to 7, and the mixture is filtered using a 0.5μm pore size filter membrane. The solid content is adjusted to 20% by adding ethanol aqueous solution to obtain boron-siloxane-grafted silica nano-dispersion.
[0034] The modified epoxy resin layer is prepared as follows: 100g of linear thermoplastic epoxy resin containing disulfide bonds is dissolved in a mixed solution of butanone and ethyl acetate (the volume ratio of butanone to ethyl acetate is 7:3), the solid content is controlled at 25%, 5g of boron-siloxane grafted silica nano-dispersion is added, ultrasonically dispersed at 25kHz for 30min, coated, and dried at 70℃ for 14h to obtain the modified epoxy resin layer.
[0035] Preparation Example 3 The preparation method of linear thermoplastic epoxy resin containing disulfide bonds is as follows: High-purity nitrogen gas is introduced into the reaction vessel to replace the air in the vessel for 30 minutes to prevent the disulfide bonds from being oxidized and decomposed at high temperature during the polymerization process. Then, 198.65g of dried bisphenol A type epoxy resin and 125.17g of dried 4,4'-dihydroxydiphenyl disulfide are added. N,N-dimethylacetamide is added to adjust the solid content to 25%. The mixture is heated to 83℃ and stirred to dissolve. After heating to 135℃, 0.64g of triphenylphosphine is added. The mixture is kept at this temperature for 7 hours under stirring. After cooling to 65℃, 500mL of acetone is added for dilution. Then, the mixture is added dropwise to deionized water under high-speed stirring. The polymer precipitates to form a precipitate. The precipitate is filtered, washed three times with anhydrous ethanol, and dried under vacuum at 85℃ for 25 hours to obtain linear thermoplastic epoxy resin containing disulfide bonds.
[0036] The preparation method of boron-siloxane-grafted silica nano-dispersion is as follows: Nitrogen gas is introduced into the reaction vessel to replace the air inside the vessel, and 6g of boric acid, 15g of dimethyldimethoxysilane and 80g of 85% ethanol aqueous solution are added under nitrogen protection. 0.3g of dibutyltin dilaurate is added, and the mixture is heated to 105℃ and refluxed for 7h. 20g of nano-silica is added, and the mixture is heated to 125℃ and ultrasonically dispersed under stirring for 11h. After cooling, the pH value is adjusted to 6, and the mixture is filtered using a 0.4μm pore size filter membrane. The solid content is adjusted to 18% by adding ethanol aqueous solution to obtain boron-siloxane-grafted silica nano-dispersion.
[0037] The modified epoxy resin layer is prepared as follows: 100g of linear thermoplastic epoxy resin containing disulfide bonds is dissolved in a mixed solution of butanone and ethyl acetate (the volume ratio of butanone to ethyl acetate is 7:3), the solid content is controlled at 25%, 4g of boron-siloxane grafted silica nano-dispersion is added, ultrasonically dispersed at 23kHz for 30min, coated, and dried at 65℃ for 13h to obtain the modified epoxy resin layer.
[0038] Preparation Example 4 The preparation method of linear thermoplastic epoxy resin containing disulfide bonds is as follows: High-purity nitrogen gas is introduced into the reaction vessel to replace the air in the vessel for 30 minutes to prevent the disulfide bonds from being oxidized and decomposed at high temperature during the polymerization process. Then, 199.34 g of dried bisphenol A type epoxy resin and 125.17 g of dried 4,4'-dihydroxydiphenyl disulfide are added. N,N-dimethylacetamide is added to adjust the solid content to 28%. The mixture is heated to 83°C and stirred to dissolve. After heating to 138°C, 0.81 g of triphenylphosphine is added. The mixture is kept at this temperature for 7.5 h under stirring. After cooling to 65°C, 500 mL of acetone is added for dilution. Then, the mixture is added dropwise to deionized water under high-speed stirring. The polymer precipitates to form a precipitate. The precipitate is filtered, washed three times with anhydrous ethanol, and dried under vacuum at 85°C for 25 h to obtain linear thermoplastic epoxy resin containing disulfide bonds.
[0039] The preparation method of boron-siloxane-grafted silica nanodispersion is as follows: Nitrogen gas is introduced into the reaction vessel to replace the air inside the vessel, and 6g of boric acid, 18g of dimethyldimethoxysilane and 82g of 85% (w / w) ethanol aqueous solution are added under nitrogen protection. 0.35g of dibutyltin dilaurate is added, and the mixture is heated to 105℃ and refluxed for 7h. 22g of nano silica is added, and the mixture is heated to 125℃ and ultrasonically dispersed under stirring for 11h. After cooling, the pH value is adjusted to 6, and the mixture is filtered using a 0.4μm pore size filter membrane. The solid content is adjusted to 18% by adding ethanol aqueous solution to obtain the boron-siloxane-grafted silica nanodispersion.
[0040] The modified epoxy resin layer is prepared as follows: 100g of linear thermoplastic epoxy resin containing disulfide bonds is dissolved in a mixed solution of butanone and ethyl acetate (the volume ratio of butanone to ethyl acetate is 7:3), the solid content is controlled at 25%, 4.5g of boron-siloxane grafted silica nano-dispersion is added, ultrasonically dispersed at 23kHz for 30min, coated, and dried at 65℃ for 13h to obtain the modified epoxy resin layer.
[0041] Preparation Example 5 The preparation method of linear thermoplastic epoxy resin containing disulfide bonds is as follows: High-purity nitrogen gas is introduced into the reaction vessel to replace the air in the vessel for 30 minutes to prevent the disulfide bonds from being oxidized and decomposed at high temperature during the polymerization process. Then, 200.35 g of dried bisphenol A type epoxy resin and 125.17 g of dried 4,4'-dihydroxydiphenyl disulfide are added. N,N-dimethylacetamide is added to adjust the solid content to 28%. The mixture is heated to 83°C and stirred to dissolve. After heating to 135°C, 0.81 g of triphenylphosphine is added. The mixture is kept at this temperature for 7 hours under stirring. After cooling to 65°C, 500 mL of acetone is added for dilution. Then, the mixture is added dropwise to deionized water under high-speed stirring. The polymer precipitates to form a precipitate. The precipitate is filtered, washed three times with anhydrous ethanol, and dried under vacuum at 85°C for 25 hours to obtain linear thermoplastic epoxy resin containing disulfide bonds.
[0042] The preparation method of boron-siloxane-grafted silica nano-dispersion is as follows: Nitrogen gas is introduced into the reaction vessel to replace the air inside the vessel, and 7g of boric acid, 16g of dimethyldimethoxysilane and 80g of 85% (w / w) ethanol aqueous solution are added under nitrogen protection. 0.35g of dibutyltin dilaurate is added, and the mixture is heated to 105℃ and refluxed for 7h. 21g of nano-silica is added, and the mixture is heated to 125℃ and ultrasonically dispersed under stirring for 11h. After cooling, the pH value is adjusted to 6, and the mixture is filtered using a 0.4μm pore size filter membrane. The solid content is adjusted to 18% by adding ethanol aqueous solution to obtain the boron-siloxane-grafted silica nano-dispersion.
[0043] The modified epoxy resin layer is prepared as follows: 100g of linear thermoplastic epoxy resin containing disulfide bonds is dissolved in a mixed solution of butanone and ethyl acetate (the volume ratio of butanone to ethyl acetate is 7:3), the solid content is controlled at 25%, 4g of boron-siloxane grafted silica nano-dispersion is added, ultrasonically dispersed at 23kHz for 30min, coated, and dried at 65℃ for 13h to obtain the modified epoxy resin layer.
[0044] Preparation Example 6 The modified UTG layer was prepared as follows: At room temperature, a 500W atmospheric pressure argon-oxygen mixed plasma was used to scan the upper and lower surfaces of the UTG for 25 seconds to obtain surface-treated UTG. 3 mol of γ-glycidyl etheroxypropyltrimethoxysilane and 1 mol of bis-[3-(triethoxysilyl)propyl]-disulfide were dissolved in 500 mL of a 65% isopropanol aqueous solution. Glacial acetic acid was added to adjust the pH to 4.5, and the solution was stirred for 2 hours to obtain a composite silane hydrolysate. The surface-treated UTG was immersed in the composite silane hydrolysate for 30 seconds, then removed and vacuum-dried at 110℃ for 15 minutes to obtain the modified UTG layer.
[0045] Preparation Example 7 The modified UTG layer was prepared as follows: At room temperature, a 600W atmospheric pressure argon-oxygen mixed plasma was used to scan the upper and lower surfaces of the UTG for 30 seconds to obtain surface-treated UTG. 5 mol of γ-glycidyl etheroxypropyltrimethoxysilane and 1 mol of bis-[3-(triethoxysilyl)propyl]-disulfide were dissolved in 500 mL of a 70% isopropanol aqueous solution. Glacial acetic acid was added to adjust the pH to 5.0, and the solution was stirred for 2.5 h to obtain a composite silane hydrolysate. The surface-treated UTG was immersed in the composite silane hydrolysate for 60 seconds, then removed and vacuum-dried at 120℃ for 20 min to obtain the modified UTG layer.
[0046] Preparation Example 8 The modified UTG layer was prepared as follows: At room temperature, a 550W atmospheric pressure argon-oxygen mixed plasma was used to scan the upper and lower surfaces of the UTG for 28 seconds to obtain surface-treated UTG. 4 mol of γ-glycidyl etheroxypropyltrimethoxysilane and 1 mol of bis-[3-(triethoxysilyl)propyl]-disulfide were dissolved in 500 mL of a 68% isopropanol aqueous solution. Glacial acetic acid was added to adjust the pH to 4.7, and the solution was stirred for 2.4 h to obtain a composite silane hydrolysate. The surface-treated UTG was immersed in the composite silane hydrolysate for 40 seconds, then removed and vacuum-dried at 115℃ for 17 min to obtain the modified UTG layer.
[0047] Preparation Example 9 The modified UTG layer was prepared as follows: At room temperature, a 580W atmospheric pressure argon-oxygen mixed plasma was used to scan the upper and lower surfaces of the UTG for 27 seconds to obtain surface-treated UTG. 4.2 mol of γ-glycidyl etheroxypropyltrimethoxysilane and 1 mol of bis-[3-(triethoxysilyl)propyl]-disulfide were dissolved in 500 mL of a 67% isopropanol aqueous solution. Glacial acetic acid was added to adjust the pH to 4.8, and the solution was stirred for 2.2 h to obtain a composite silane hydrolysate. The surface-treated UTG was immersed in the composite silane hydrolysate for 50 seconds, then removed and vacuum-dried at 115℃ for 18 min to obtain the modified UTG layer.
[0048] Preparation Example 10 The modified UTG layer was prepared as follows: At room temperature, a 540W atmospheric pressure argon-oxygen mixed plasma was used to scan the upper and lower surfaces of the UTG for 29 seconds to obtain surface-treated UTG. 3.5 mol of γ-glycidyl etheroxypropyltrimethoxysilane and 1 mol of bis-[3-(triethoxysilyl)propyl]-disulfide were dissolved in 500 mL of a 67% isopropanol aqueous solution. Glacial acetic acid was added to adjust the pH to 4.8, and the solution was stirred for 2.3 h to obtain a composite silane hydrolysate. The surface-treated UTG was immersed in the composite silane hydrolysate for 50 seconds, then removed and vacuum-dried at 115℃ for 18 min to obtain the modified UTG layer.
[0049] Example 1 A high-impact protective film for a UTG foldable display screen comprises, from top to bottom, a base film layer, a modified epoxy resin layer, a modified UTG layer, another modified epoxy resin layer, another modified UTG layer, a modified epoxy resin layer, and an OCA adhesive film layer. The base film layer has a thickness of 25 μm, the modified epoxy resin layer has a thickness of 20 μm, the modified UTG layer has a thickness of 30 μm, and the OCA adhesive film layer has a thickness of 40 μm. The modified epoxy resin layer was prepared in Preparation Example 1, and the modified UTG layer was prepared in Preparation Example 6.
[0050] The specific preparation method is as follows: the base film layer is bonded to the modified epoxy resin layer, and then the modified UTG layer, modified epoxy resin layer, modified UTG layer, modified epoxy resin layer and OCA adhesive film layer are bonded sequentially on the modified epoxy resin layer. The bonding is performed by a fully automatic hot press bonding machine, and the film is cut to obtain a high impact-resistant protective film for UTG folding display screen.
[0051] Example 2 A high-impact protective film for a UTG foldable display screen comprises, from top to bottom, a base film layer, a modified epoxy resin layer, a modified UTG layer, another modified epoxy resin layer, a modified UTG layer, a modified epoxy resin layer, and an OCA adhesive film layer. The thickness of the base film layer is 75 μm, the thickness of the modified epoxy resin layer is 60 μm, the thickness of the modified UTG layer is 70 μm, and the thickness of the OCA adhesive film layer is 80 μm. The modified epoxy resin layer was prepared in Preparation Example 2, and the modified UTG layer was prepared in Preparation Example 7.
[0052] The specific preparation method is as follows: the base film layer is bonded to the modified epoxy resin layer, and then the modified UTG layer, modified epoxy resin layer, modified UTG layer, modified epoxy resin layer and OCA adhesive film layer are bonded sequentially on the modified epoxy resin layer. The bonding is performed by a fully automatic hot press bonding machine, and the film is cut to obtain a high impact-resistant protective film for UTG folding display screen.
[0053] Example 3 A high-impact protective film for a UTG foldable display screen comprises, from top to bottom, a base film layer, a modified epoxy resin layer, a modified UTG layer, another modified epoxy resin layer, a modified UTG layer, a modified epoxy resin layer, and an OCA adhesive film layer. The base film layer has a thickness of 32 μm, the modified epoxy resin layer has a thickness of 25 μm, the modified UTG layer has a thickness of 41 μm, and the OCA adhesive film layer has a thickness of 50 μm. The modified epoxy resin layer was prepared in Preparation Example 3, and the modified UTG layer was prepared in Preparation Example 8.
[0054] The specific preparation method is as follows: the base film layer is bonded to the modified epoxy resin layer, and then the modified UTG layer, modified epoxy resin layer, modified UTG layer, modified epoxy resin layer and OCA adhesive film layer are bonded sequentially on the modified epoxy resin layer. The bonding is performed by a fully automatic hot press bonding machine, and the film is cut to obtain a high impact-resistant protective film for UTG folding display screen.
[0055] Example 4 A high-impact protective film for a UTG foldable display screen comprises, from top to bottom, a base film layer, a modified epoxy resin layer, a modified UTG layer, another modified epoxy resin layer, another modified UTG layer, a modified epoxy resin layer, and an OCA adhesive film layer. The thickness of the base film layer is 43 μm, the thickness of the modified epoxy resin layer is 35 μm, the thickness of the modified UTG layer is 52 μm, and the thickness of the OCA adhesive film layer is 63 μm. The modified epoxy resin layer was prepared in Preparation Example 4, and the modified UTG layer was prepared in Preparation Example 9.
[0056] The specific preparation method is as follows: the base film layer is bonded to the modified epoxy resin layer, and then the modified UTG layer, modified epoxy resin layer, modified UTG layer, modified epoxy resin layer and OCA adhesive film layer are bonded sequentially on the modified epoxy resin layer. The bonding is performed by a fully automatic hot press bonding machine, and the film is cut to obtain a high impact-resistant protective film for UTG folding display screen.
[0057] Example 5 A high-impact protective film for a UTG foldable display screen comprises, from top to bottom, a base film layer, a modified epoxy resin layer, a modified UTG layer, another modified epoxy resin layer, another modified UTG layer, a modified epoxy resin layer, and an OCA adhesive film layer. The thickness of the base film layer is 53 μm, the thickness of the modified epoxy resin layer is 48 μm, the thickness of the modified UTG layer is 52 μm, and the thickness of the OCA adhesive film layer is 62 μm. The modified epoxy resin layer was prepared in Preparation Example 5, and the modified UTG layer was prepared in Preparation Example 10.
[0058] The specific preparation method is as follows: the base film layer is bonded to the modified epoxy resin layer, and then the modified UTG layer, modified epoxy resin layer, modified UTG layer, modified epoxy resin layer and OCA adhesive film layer are bonded sequentially on the modified epoxy resin layer. The bonding is performed by a fully automatic hot press bonding machine, and the film is cut to obtain a high impact-resistant protective film for UTG folding display screen.
[0059] Comparative Example 1 The protective film and its preparation method in this comparative example are similar to those in Example 4. The difference between this comparative example and Example 4 is that bisphenol A type epoxy resin E-51 is used instead of linear thermoplastic resin containing disulfide bonds in this comparative example.
[0060] Comparative Example 2 The protective film and its preparation method in this comparative example are similar to those in Example 4. The difference between this comparative example and Example 4 is that boron-siloxane grafted silica nano-dispersion was not added in the preparation method of the modified epoxy resin layer in this comparative example.
[0061] Comparative Example 3 The protective film and its preparation method in this comparative example are similar to those in Example 4. The difference between this comparative example and Example 4 is that a nano silica dispersion is used instead of a boron-siloxane grafted silica nano dispersion in this comparative example. The preparation method of the nano silica dispersion is as follows: nano silica is added to an 85% (w / w) ethanol aqueous solution, the solid content is controlled at 18%, and the mixture is ultrasonically dispersed to obtain a nano silica dispersion.
[0062] Comparative Example 4 The protective film and its preparation method in this comparative example are similar to those in Example 4. The difference between this comparative example and Example 4 is that UTG is used instead of the modified UTG layer in this comparative example.
[0063] Test case Test samples: Protective films prepared in Examples 1-5 and Comparative Examples 1-4; Adhesion test: The foldable screen protector is adhered to the bending test machine. The adhesion surface should be flat, tight, and free of bubbles and wrinkles (Microk SA6500 mobile phone bending durability test machine). If the protective film at the bending point of the test machine shows deformation, cracking, or peeling, the bending test is stopped and the number of bends is recorded. Impact resistance test: A steel ball with a diameter of 20mm and a mass of 32.6g was dropped freely from different heights onto the foldable screen with the protective film attached, and the height at which the breakage or bright spots appeared was recorded. Transmittance test: Transmittance in the wavelength range of 400~700nm was measured using a UV-Vis spectrophotometer.
[0064] The experimental results are shown in Table 1.
[0065] Table 1 Performance Test Results
[0066] Based on the experimental data from Examples 1-5 and Comparative Example 1, it can be seen that the disulfide bonds in the modified epoxy resin layer can effectively improve the interfacial bonding force between the modified UTG layer and the modified epoxy resin layer, thereby improving the adhesion performance between the modified UTG layer and the modified epoxy resin layer. Based on the experimental data from Examples 1-5, Comparative Example 2 and Comparative Example 3, it can be seen that the boron-siloxane-grafted nano-silica distributed in the modified epoxy resin layer can effectively improve the impact resistance of the protective film, indicating that boron-siloxane undergoes [reaction / reaction] when subjected to stress. Acute cross-linking and rapid dispersion of stress concentration occur, while unmodified nano-silica increases the haze of the protective film and reduces its light transmittance due to uneven dispersion. According to the experimental data of Examples 1-5 and Comparative Example 4, the use of γ-glycidyl etheroxypropyltrimethoxysilane and bis-[3-(triethoxysilyl)propyl]-disulfide to form a transition layer on the UTG surface in this invention can effectively improve the bonding force between the modified UTG layer and the modified epoxy resin layer, thereby improving the adhesion and bending resistance of the protective film.
[0067] In addition, the present invention also conducted infrared spectroscopy tests on the linear thermoplastic epoxy resin containing disulfide bonds obtained in Preparation Example 4, and the test results are shown in [Figure 4]. Figure 1 .Depend on Figure 1 It can be seen that at 3395cm -1 The characteristic peak of the secondary hydroxyl group formed by ring opening appeared at 2902 cm⁻¹. -1 The characteristic peak of the =CH group in the benzene ring appeared at 2872 cm⁻¹. -1 Characteristic peaks of saturated CH in -CH3 and -CH2- appeared at 1658 cm⁻¹. -1 The characteristic peak of C=C in the benzene ring appeared at 1395 cm⁻¹. -1 The characteristic peak of ether bonds appeared at 1190 cm⁻¹. -1 The characteristic peak of aliphatic ether appeared at 792 cm⁻¹. -1 The characteristic peak of para-substitution =CH of the benzene ring appeared at 541 cm⁻¹. -1 The presence of a characteristic peak for disulfide bonds indicates that disulfide bonds have been successfully introduced into the molecular structure of linear thermoplastic epoxy resin.
[0068] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A high-impact protective film for a UTG foldable display screen, characterized in that, From top to bottom, it includes a base film layer, a modified epoxy resin layer, a modified UTG layer, a modified epoxy resin layer, a modified UTG layer, a modified epoxy resin layer, and an OCA adhesive film layer. The modified epoxy resin layer is prepared by dissolving a linear thermoplastic epoxy resin containing disulfide bonds in a mixed solution of butanone and ethyl acetate, adding boron-siloxane grafted silica nano-dispersion, ultrasonically dispersing it evenly, coating it, and drying it to obtain the modified epoxy resin layer. The preparation method of linear thermoplastic epoxy resin containing disulfide bonds is as follows: Nitrogen gas is introduced into the reaction vessel to replace the air in the vessel, then bisphenol A type epoxy resin and 4,4'-dihydroxydiphenyl disulfide are added, N,N-dimethylacetamide is added to adjust the solid content to 20%-30%, the mixture is heated to 80-85℃ and stirred to dissolve, the temperature is raised to 130-140℃ and triphenylphosphine is added, the mixture is kept at the temperature for 6-8 hours under stirring, the temperature is cooled to 60-70℃, acetone is added for dilution, and then the mixture is added dropwise to deionized water under high-speed stirring. The polymer precipitates to form a precipitate, which is then filtered, washed, and dried to obtain linear thermoplastic epoxy resin containing disulfide bonds. The preparation method of boron-siloxane-grafted silica nano-dispersion is as follows: nitrogen gas is introduced into the reaction vessel to replace the air in the vessel, and boric acid, dimethyldimethoxysilane and ethanol aqueous solution are added under nitrogen protection. Dibutyltin dilaurate is added, the temperature is raised to 100-110℃ and refluxed for 6-8 hours. Nano-silica is added, the temperature is raised to 120-130℃, and ultrasonic dispersion is carried out under stirring for 10-12 hours. After cooling, the pH value is adjusted to 5-7, filtered, and ethanol aqueous solution is added to adjust the solid content to 15%-20% to obtain boron-siloxane-grafted silica nano-dispersion. The modified UTG layer is prepared as follows: the upper and lower surfaces of the UTG are scanned and treated by atmospheric pressure argon-oxygen mixed plasma at room temperature to obtain surface-treated UTG; γ-glycidyl etheroxypropyltrimethoxysilane and bis-[3-(triethoxysilyl)propyl]-disulfide are dissolved in an aqueous solution of isopropanol, the pH is adjusted to 4.5-5.0, and the solution is stirred for 2-2.5 h to obtain a composite silane hydrolysate; the surface-treated UTG is immersed in the composite silane hydrolysate for 30-60 s, and then vacuum dried at 110-120℃ for 15-20 min to obtain the modified UTG layer.
2. The high impact-resistant protective film for UTG foldable displays according to claim 1, characterized in that, The molar ratio of the epoxy group in the bisphenol A epoxy resin to the phenolic hydroxyl group in 4,4'-dihydroxydiphenyl disulfide is (1.02-1.05):1; the amount of triphenylphosphine used is 0.1%-0.3% of the total mass of the bisphenol A epoxy resin and 4,4'-dihydroxydiphenyl disulfide.
3. The high impact-resistant protective film for UTG foldable displays according to claim 1, characterized in that, The mass percentages of boric acid, dimethyldimethoxysilane, ethanol aqueous solution, dibutyltin dilaurate, and nano silica are as follows: boric acid 3-8 parts, dimethyldimethoxysilane 10-20 parts, ethanol aqueous solution 70-85 parts, dibutyltin dilaurate 0.1-0.5 parts, and nano silica 15-25 parts; the mass percentage of the ethanol aqueous solution is 80%-90%.
4. The high impact-resistant protective film for UTG foldable displays according to claim 1, characterized in that, In the preparation method of the modified epoxy resin layer, the amount of boron-siloxane grafted silica is 3%-5% of the mass of the linear thermoplastic epoxy resin containing disulfide bonds.
5. The high impact-resistant protective film for UTG foldable displays according to claim 1, characterized in that, The power of the atmospheric pressure argon-oxygen mixed plasma is 500-600W, and the scanning time is 25-30s; the molar ratio of γ-glycidyl etheroxypropyltrimethoxysilane and bis-[3-(triethoxysilyl)propyl]-disulfide is (3-5):1; the mass percentage of the isopropanol aqueous solution is 65%-70%.
6. The high impact-resistant protective film for UTG foldable displays according to claim 1, characterized in that, The base film layer is a polyimide resin film; the OCA adhesive film layer is an acrylic folded OCA adhesive film; the thickness of the base film layer is 25-75μm, the thickness of the modified epoxy resin layer is 20-60μm, the thickness of the modified UTG layer is 30-70μm, and the thickness of the OCA adhesive film layer is 40-80μm.
7. The method for preparing a high-impact-resistant protective film for a UTG foldable display screen according to any one of claims 1-6, characterized in that, Specifically, the base film layer is bonded to the modified epoxy resin layer, and then a modified UTG layer, a modified epoxy resin layer, a modified UTG layer, a modified epoxy resin layer and an OCA adhesive film layer are bonded sequentially on the modified epoxy resin layer. The bonding is performed by a fully automatic hot press laminating machine, and the film is then cut to obtain a high-impact protective film for UTG folding displays.
Citation Information
Patent Citations
Flexible screen cover plate, flexible screen and foldable electronic equipment
CN119445980A
Optical adhesive film and preparation method thereof, flexible cover plate and electronic equipment
CN117820980A
Flexible OCA optical cement, folding mobile phone outer screen and preparation method of folding mobile phone outer screen
CN118126656A
